ANALISIS IMPLEMENTASI KEBIJAKAN PROGRAM KELUARGA HARAPAN (PKH) DALAM MENANGGULANGI KEMISKINAN DI KECAMATAN KEMILING KOTA BANDAR LAMPUNG - Achmad Suharyo; Siti Khomariyati (e-JKPP, 2020)
Problem Formulation In this study, namely (1) How the Implementation of Family Hope Program Policy in Tackling Poverty in Kemiling District Bandar Lampung City. (2) What aspects support and hinder the implementation of the Family Hope Program  Policy in Tackling Poverty in Kemiling District, Bandar Lampung City.The research method used is qualitative descriptive analysis method. The use of this method is to describe the Implementation of the Family Hope Program  Policy in Reducing Poverty in the Kemiling District of Bandar Lampung City, assessing qualitatively, how all data is obtained directly from informants in the field using interviews and observation.The results showed that the Implementation of the Family Hope Program  Policy in Reducing Poverty in the Kemiling District of Bandar Lampung City, had been carried out through the dimensions of (1) Communication, the Family Hope Program, had been socialized, although there were still people who wanted better service. (2) Human resources, executors / assistants are relatively lacking, (3) Disposition / attitude of implementers, which have not been optimal in implementing policies, (4) Bureaucratic structure, which seems to lack the function of each structure, so it does not run optimally.Aspects that hinder, namely (1) Aspects of Communication aspects that are still relatively weak, which is characterized by a lack of socialization of the implementation of the Family Hope Program, (2) Lack of Human Resources, Implementers / Companion of the Family Hope Program, requires a relatively large quantity or number of implementers / assistants to manage the family hope program, which so far the number of implementers / assistants assigned to manage the family hope program is relatively small so that it cannot supervise well and reach out to the community get a family of hope program, (3) Relatively lack of supervision of the implementation of the family of hope program  in Kemiling District so that the existing problems are not immediately responded by the executor / assistant or the government.